Analisis Gap Kompetensi Calon Sekretaris Dan Sekretaris Pimpinan Pada Perusahaan Di Indonesia - sofiatiningsih sofiatiningsih; Fenny Damayanti (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
Government has issued a Regulation of the Minister of Manpower of the Republic of Indonesia No. 2, 2016 concerning the National Work Competency Standardization. The competency standard is expected to be a reference for prospective and existing employees to understand the appropriate competency standards needed in a company. This study wants to find out how the competency gap between secretary candidates and those who are working as secretary in companies in Indonesia. This research can be a reference that secretarial competencies must be improved in order to met with company’expectation. Besides, it can provide inputs to many universities to improve the competencies of their graduates. This research uses a qualitative method with a descriptive approach. The results shows that the competency of secretary candidates needed is attitude and for those who are working as a secretary, inisiative is the important competence and as expected by certain companies. Therefore, the gap between the competency for secretary candidates and a secretary is a continuous competency, it would be best if attitude/personality development could be inserted in every course given in universities. Furthermore, giving more case study in the learning method will enable them to think creatively and innovatively.